2018
DOI: 10.1007/978-3-319-99828-2_17
|View full text |Cite
|
Sign up to set email alerts
|

Usability Characteristics of Security and Privacy Tools: The User’s Perspective

Abstract: Use of security and privacy tools is still limited for various reasons, including usability issues. This paper analyses usability characteristics of security and privacy tools by drawing on relevant literature and employing scenario-based questionnaires and interviews with 150 users to capture their views. Based on users' feedback, we analyse the role of usability characteristics and identify critical issues such as transparency, control of personal data, design and accessibility and consistency. This paper pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…ISO 27005:2011 (in Section 9.2 and Annex F) provides general directions on the criteria which security managers need to consider when selecting the appropriate controls during the risk management process, such as ease of use. Whilst usability plays an important role in motivating users to use technologies (Nielsen, 1994), security tools are still not usable enough (Whitten and Tygar, 1999; Topa and Karyda, 2018; Vemou et al , 2015). This is an on-going challenge for researchers and designers, who need to design and develop usable security tools.…”
Section: Discussion: Issues and Challenges For Security Managementmentioning
confidence: 99%
“…ISO 27005:2011 (in Section 9.2 and Annex F) provides general directions on the criteria which security managers need to consider when selecting the appropriate controls during the risk management process, such as ease of use. Whilst usability plays an important role in motivating users to use technologies (Nielsen, 1994), security tools are still not usable enough (Whitten and Tygar, 1999; Topa and Karyda, 2018; Vemou et al , 2015). This is an on-going challenge for researchers and designers, who need to design and develop usable security tools.…”
Section: Discussion: Issues and Challenges For Security Managementmentioning
confidence: 99%
“…To address the first research question a thorough review and analysis of related literature in the field of information security behavior was conducted, in order to establish a comprehensive picture of all the documented factors related to security behavior (Topa & Karyda, 2015;Topa & Karyda, 2016); through this analysis areas were identified that are not sufficiently explored, such as the role of usability of security technology. This aspect was further explored through a usability survey (Topa & Karyda, 2018). By combining the findings from both the literature review and the survey a Technological-Organisational-Individual framework is developed.…”
Section: Information Security Policy Compliance and Security Behaviour: Backgroundmentioning
confidence: 99%
“…There are a number of important technological aspects which are relevant to the usability of security tools, which according to literature may impact on security behaviour and consequently on ISP compliance (Topa & Karyda, 2018). It is therefore essential that security managers be made aware of these security behaviour determinants and take the appropriate steps to ensure that any security tools used by the organisation have optimum usability.…”
Section: Technological Aspectsmentioning
confidence: 99%
See 2 more Smart Citations